2021
DOI: 10.1007/s10877-021-00715-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of COVID-19 epidemic on vital signs in hospitalized patients: a pre-post heat-map study from a large teaching hospital

Abstract: The Lombardy SARS-CoV-2 outbreak in February 2020 represented the beginning of COVID-19 epidemic in Italy. Hospitals were flooded by thousands of patients with bilateral pneumonia and severe respiratory, and vital sign derangements compared to the standard hospital population. We propose a new visual analysis technique using heat maps to describe the impact of COVID-19 epidemic on vital sign anomalies in hospitalized patients. We conducted an electronic health record study, including all confirmed COVID-19 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Out of 155 cases, 66.5% were males, and 33.5% were females. A similar study conducted by Caruso PF et al [5] showed that male was 66%, and female patients were 34 %. [11] showed post-COVID-19 at admission [120.9/78.5mmHg] & discharge [126.5/81.8 mmHg] was high.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…Out of 155 cases, 66.5% were males, and 33.5% were females. A similar study conducted by Caruso PF et al [5] showed that male was 66%, and female patients were 34 %. [11] showed post-COVID-19 at admission [120.9/78.5mmHg] & discharge [126.5/81.8 mmHg] was high.…”
Section: Resultssupporting
confidence: 51%
“…In this study the mean respiratory rate(RR), Heart Rate (HR), Temparature, saturated partial pressure of oxygen (SPO2) in these study at admission and discharge was 21.75cpm and 20.41cpm; 84.18bpm and 79.48bpm; 98.76: 95.17% and 96.77% respectively which is higher when compare with study conducted by Caruso PF et al [5] the mean RR was 18cpm: 79 bpm: 96.8°F : SPO2 (96%).…”
Section: Resultsmentioning
confidence: 52%
“…a) Heat-map: A heat map is a data visualization technique that shows the magnitude of a phenomenon as color in two dimensions [31][32]. The color variation may be by hue or intensity, giving obvious visual cues to the reader about how the phenomenon is clustered or varies over space [38].…”
Section: B Data Visualization and Relationship In A Datasetmentioning
confidence: 99%
“…Wearable sensors measure vital signs (temperature, respiration rate, heart rate, blood pressure, and oxygen saturation Figure 2) and are linked to the HW platform MySignal. Severe derangements of signs are defined by pre-established thresholds: temperature over 37,5 °C, peripheral oxygen saturation below 90%, respiratory rate less than 10 or less than 25 breaths per minute, heart rate less than 40 bpm, and mean arterial pressure less than 65 MmHg (38). This platform is linked to the Fog-Layer mobile app.…”
Section: Covidfog: Fog Based Proposed Model For Monitoring Covid-19 P...mentioning
confidence: 99%